(3bGYOI faj GdVQQs - (3GdWHGWHGFj, GdMLI, eMeO HGbQ Hf MSf, J (B1331 (3g`s
(3ChdgG (B:s
(3GYde Cf bGYOI faj GdVQQ ef GdbhGYO GdJj LQJ aj ZjQ ehQO Ydi CdSf GdaMhd(B...s
(3BNQgG (B:s
...(3adG efGaGI HjfgeG CUdG adGHO ef CMQGR GdedGc GdePchQ aj GdJMcje hEP cGf fGOQ GdhbhY bdjd GdehVhY(B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3CUhd Gdabgs